2007
DOI: 10.1080/10245330701214384
|View full text |Cite
|
Sign up to set email alerts
|

Markers of apoptosis and proliferation related gene products as predictors of treatment outcome in childhood acute lymphoblastic leukemia

Abstract: The aim of the study is to characterize markers of apoptosis in children with acute lymphoblastic leukemia (ALL) in relation to treatment outcome of the disease. The study was performed on 34 children with ALL and 39 healthy children as a control group. Apoptosis was assessed by cell morphology; DNA fragmentation; ELISA and RT-PCR for CD95, CD95L, BcL-2 and nuclear factor-kappa B (NF-kappaB); and flow cytometry for CD95, CD40, CD49d and CD11a. Apoptosis was significantly lower in patients than controls. Apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…In accordance with our results, Hafez et al [21] demonstrated that apoptosis was lower in patients than in controls and suggested that inhibitors for the activity of Bcl-2 and NF-κB as well as stimulants to CD 95 could have a potential therapeutic benefit. Consistent with our results, Tamiya et al [22] found defects in expression of Fas antigen on leukemia cells because of mutations in Fas genes of these cells.…”
Section: Discussionsupporting
confidence: 94%
“…In accordance with our results, Hafez et al [21] demonstrated that apoptosis was lower in patients than in controls and suggested that inhibitors for the activity of Bcl-2 and NF-κB as well as stimulants to CD 95 could have a potential therapeutic benefit. Consistent with our results, Tamiya et al [22] found defects in expression of Fas antigen on leukemia cells because of mutations in Fas genes of these cells.…”
Section: Discussionsupporting
confidence: 94%
“…Studies in recent years indicate that continuous abnormal activation of NF-κB exists in various types of leukemia cells, while it has a relationship with Fas-mediated apoptosis resistance in leukemia cells [3][4][5]. NF-κB is considered to be a predictor of poor treatment outcome in childhood acute lymphoblastic leukemia, and inhibitors for the activity of NF-κB and stimulants to Fas could have a potential therapeutic benefit [6]. Many researches indicate that the sensitivity of tumor cells, such as the lymphoma cell line HuT78 and T cell line H9, to apoptosis can be enhanced by inhibiting NF-κB, but the mechanism is not clear yet [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…High Bcl-2 levels and a decrease of the Bax/Bcl-2 ratio have been associated with poor prognosis in childhood ALL in some studies. 31,32 We therefore investigated the effect of XIAP inhibitors on TRAIL-induced apoptosis in Jurkat leukemia cells with ectopic expression of Bcl-2 ( Figure 5A). Bcl-2 overexpression almost completely inhibited TRAIL-induced apoptosis (Figure 5B), consistent with the idea that type II Jurkat cells depend on the mitochondrial pathway for TRAIL-induced apoptosis.…”
Section: Xiap Inhibitors Overcome Bcl-2-mediated Resistance To Trail-mentioning
confidence: 99%